1962
DOI: 10.1161/01.cir.25.6.995
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic Occlusion of Abdominal Aortic Aneurysm Following Distal Embolization

Abstract: The second successfully treated case of sudden complete occlusion of an abdominal aortic aneurysm is presented. The thrombosis was caused by impaired run-off following an embolic occlusion of the right iliac artery. This complication is extremely rare in abdominal aortic aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

1966
1966
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 1 publication
0
4
0
4
Order By: Relevance
“…However, several of the studies reviewed have reported that combination of a relatively small aneurysm and severe occlusive disease may lead to acute thrombosis of an AAA, supporting the argument that small aneurysms in the presence of severe iliac artery occlusive disease should be resected. 3,4 Hirose et al proposed four basic mechanisms of AAA complete thrombosis: (1) associated iliac and/or infrainguinal occlusive disease, leading to AAA outflow obstruction; (2) thromboemboli, usually of cardiac origin, which may occlude the inflow 23 ; (3) sudden dislodgment of a mural thrombus, as might be provoked by trauma 13,24 , and (4) cardiac events-related hypotension and low-flow state. Hypercoagulability secondary to dehydration, neoplasm, polycythemia, etc., 4,21,25,26 as well as surgical manipulation, 20,27,28 are additional potential etiologic factors Although endovascular repair 29 and ''bridge'' thrombolytic therapy 30 have been reported in some acute cases, the preferred treatment for AAA thrombosis involves trans-or retroperitoneal surgical approach, aneurysmal sac opening and resection, complete removal of the obstructing thrombus, and prosthetic aortic repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several of the studies reviewed have reported that combination of a relatively small aneurysm and severe occlusive disease may lead to acute thrombosis of an AAA, supporting the argument that small aneurysms in the presence of severe iliac artery occlusive disease should be resected. 3,4 Hirose et al proposed four basic mechanisms of AAA complete thrombosis: (1) associated iliac and/or infrainguinal occlusive disease, leading to AAA outflow obstruction; (2) thromboemboli, usually of cardiac origin, which may occlude the inflow 23 ; (3) sudden dislodgment of a mural thrombus, as might be provoked by trauma 13,24 , and (4) cardiac events-related hypotension and low-flow state. Hypercoagulability secondary to dehydration, neoplasm, polycythemia, etc., 4,21,25,26 as well as surgical manipulation, 20,27,28 are additional potential etiologic factors Although endovascular repair 29 and ''bridge'' thrombolytic therapy 30 have been reported in some acute cases, the preferred treatment for AAA thrombosis involves trans-or retroperitoneal surgical approach, aneurysmal sac opening and resection, complete removal of the obstructing thrombus, and prosthetic aortic repair.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Hirose et al. proposed four basic mechanisms of AAA complete thrombosis: (1) associated iliac and/or infrainguinal occlusive disease , leading to AAA outflow obstruction; (2) thromboemboli , usually of cardiac origin, which may occlude the inflow 23 ; (3) sudden dislodgment of a mural thrombus, as might be provoked by trauma 13,24 , and (4) cardiac events-related hypotension and low-flow state. H ypercoagulability secondary to dehydration, neoplasm, polycythemia, etc., 4,21,25,26 as well as surgical manipulation , 20,27,28 are additional potential etiologic factors…”
Section: Discussionmentioning
confidence: 99%
“…По не кад су пр ва ма ни фе ста ци ја не ког си стем ског обо ље ња, као што су lu pus erythe ma to sus, скле ро дер ми ја, Реј но ов (Raynaud) фе но мен, Елерс-Дан ло сов (Ehlers-Dan los) син дром и Мар фа нов (Mar fan) син дром, те по ре ме ћа ја ко а гу ла бил но сти кр ви или ва ску ли ти са [1,2]. Кли нич ки ја сна ис хе ми ја де ла сто па ла пра ће на бо лом, хи по е сте зи јом и ли ви ди те том пр сти ју ни је чест знак [3], али је мо гу ћа ра на ма ни фе ста ци ја дис тал не ар те риј ске ем бо ли за ци је (3-29%) из ане у ри змат ске вре ће аб до ми нал не аор те (ААА) [4,5,6]. Ве ли ки број тром бо тич них ма са, њи хо ва рас тре си тост и мо гу ћа фраг мен та ци ја уну тар са ме ане у ри зме мо гу ћи су узро ци ове ком пли ка ци је [7,8,9].…”
Section: уводunclassified
“…(2) Thromboemboli, which are usually of cardiac origin secondary to the myocardial infarction,5,9,12 or atrial fibrillation,9 may occlude the inflow of the aneurysm, followed by complete obstruction. (3) Sudden dislodgment of a mural thrombus in the aneurysm may occlude the outflow and lead to retrograde obstructionism Studies on acute thrombosed aneurysm associated with a fall or abdominal trauma can be explained by distal embolization of a fragment of a mural thrombus.13,17 (4) Hypotension and a temporary low-flow state due to cardiac events may initiate intravascular thrombosis and cause total occlusion of an aneurysm.5 S Several studies have reported that combination of a relatively small aneurysm and severe occlusive disease may lead to acute thrombosis of an AAA.4,8,9,14 However, our literature review revealed that the risk of thrombosis was independent of the size of the aneurysm. Peripheral vascular disease and cardiac disease are the major risk factors for AAA thrombosis.…”
Section: Review Of Literaturementioning
confidence: 99%